Beginning ASP.NET 2.0 Databases - Foggon, Damien (Apress, 2012)
Welcome to the introduction. From this point on, you’ll discover the amazing world of ADO.NET, inanimate computer desks, late-night coding sessions, evil bugs, functions, methods, properties, and data. Seriously though, welcome to the world of databases in ASP.NET. The idea for this kind of book isn’t new, but if you’re trying to learn something for the first time, having it constantly spelled out to you in a stodgy, primary-school-history-teacher-learnthese- dates-by-rote style probably won’t help. Therefore, you’ll find one joke per 50 pages to this book to break up the monotony. Actually, a confession here: I studiously spent several years avoiding anything to do with databases because, despite my love of things techie, I always perceived them to be even more techie than other server products and operating systems. Come on, system administrators defer to database administrators, who have to wear white lab coats, have foreheads the size of Mount Rushmore to hold their huge brains, and speak in some additional language only they understand to commune directly with their charges, don’t they? Of course not. Thanks to a little nudging and handholding, I can now build data-driven Web sites. These Web sites use databases and other sources of information to define what they present to a user and how they present it, and to learn how the user would like it to work.